Eksplorasi Tren Dan Dinamika Penelitian Global Mengenai Tata Kelola Teknologi Informasi - Putri, Elivia Pasma; Prawira, Muhammad Arya Satria (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The development of the 21st century has made human life dependent on information technology, including organizations. This certainly encourages every organization, both in the public and private sectors, to carry out more mature planning through IT governance. In recent decades, the issue of IT governance has developed with various frameworks and standards for implementing global information technology, such as ITSM, ITIL, COBIT, ISO 20000, ISO 38500, and so on. Meanwhile, in public sector organizations, IT governance is implemented through Presidential Regulation Number 95 of 2018 concerning the Electronic-Based Government System (SPBE), also known as E-Government. However, based on research conducted by the author using a simple quantitative method through the assistance of the Scival Platform and bibliometric analysis, it has shown that the issue of IT governance over the past 5 years (2020-2025) has experienced a significant decline of 73%. Therefore, it is very necessary for every academic to conduct further research as a form of developing science and making a global contribution to further research.